PERWUJUDAN DEMOKRASI PANCASILA DALAM PEMEBELAJARAN PPKn ATAS PUTUSAN (MK. NO 65/PUU – XXI / 2023) TERHADAP KAMPANYE DI LEMBAGA PENDIDIKAN - Feka, Yanuarius Sani; Keraf, Fransiskus M. P.; Taena, Emanuel Tati; Kolo, Adriana (Jurnal Pendidikan Indonesia : Teori, Penelitian, dan Inovasi, 2025)
Participation in the implementation of general elections for democratic countries as a manifestation of the application of popular sovereignty that has the highest power. Participation for the category of novice voter groups in exercising their right to vote must be fortified with knowledge about the implementation of general elections, because Pancasila and Civic Education (PPKn) can provide a wealth of knowledge of Pancasila democratic education, especially in the implementation of general elections. Another goal is that the values and principles of democracy can be practiced directly by novice voters such as students or SMA / MK Class XII students. To find out how the form of Pancasila democracy in Civics learning on the decision of the Constitutional Court. No. 65/PUU-XXI/2023 requires analysis and impact on the form of implementation of Civics Learning on Campaigns in Educational Institutions. The method used is qualitative research in analyzing the manifestation of Pancasila democracy through Civics learning on the Constitutional Court's decision No.65 / PUU-XXI / 2023 from the results of the study it was found that the discussion of material submitted to SMA / MK students about democracy has started from class X to class XII. Knowledge of the democratic implementation system that is carried out, especially the implementation of regional elections, on the Constitutional Court decision No.65 / PUU-XXI / 2023 which provides space for campaigns in educational institutions is still a confusion of educators in schools due to the lack of socialization and regulations governing the follow-up to the Constitutional Court's decision. The main purpose of general elections is to provide opportunities for Indonesian citizens to express their aspirations and elect leaders who represent the rights of the people in the government. The Constitutional Court's decision No.65/PUU-XXI/2023 is in line with the role of high school students as agents of control who are responsible for overseeing Pancasila democracy. The importance of socialization and regulation from the government for SMA / MK schools as an implementation of the Constitutional Court's decision.ABSTRAKPartisipasi dalam pelaksanaan pemilihan umum bagi negara demokrasi sebagai wujud dari penerapan kedaulatan rakyat yang memiliki kekuasaan tertinggi. Partisipasi bagi kategori kelompok pemilih pemula dalam menggunakan hak pilih harus dibentengi dengan pengetahuan tentang pelaksanaan pemilihan umum, sebab Pendidikan Pancasila dan Kewarganegaraan (PPKn) dapat memberikan khasanah pengetahuan pendidikan demokrasi Pancasila terutama dalam pelaksanaan pemilihan umum. Tujuan lain agar nilai dan prinsip demokrasi dapat dipraktikkan secara langsung oleh pemilih pemula seperti siswa atau pelajar SMA/MK Kelas XII. Untuk mengetahui bagaimana wujud demokrasi Pancasila dalam pembelajaran PPKn atas putusan MK. No. 65/PUU-XXI/2023 diperlukan analisis dan dampak terhadap bentuk implementasi Pembelajaran PPKn Terhadap Kampanye di Lembaga Pendidikan. Metode yang digunakan adalah penelitian kualitatif dalam menganalisis perwujudan demokrasi Pancasila lewat pembelajaran PPKn atas putusan MK No.65/PUU-XXI/2023 dari hasil penelitian ditemukan bahwa pembahasan materi yang disampaikan kepada siswa SMA/MK tentang demokrasi sudah dimulai dari kelas X sampai kelas XII. Pengetahuan terhadap sistem pelaksanaan demokrasi yang dijalankan terutama pelaksanaan pemilihan kepala daerah, atas putusan MK No.65/PUU-XXI/2023  yang memberikan ruang terhadap kampanye di Lembaga Pendidikan  masih menjadi kebingungan dari para pendidik di sekolah karena kurangnya sosialisasi dan regulasi yang mengatur atas tindak lanjut dari putusan MK. Tujuan utama dari pemilihan umum adalah memberikan kesempatan kepada warga negara Indonesia untuk menyampaikan aspirasi dan memilih para pemimpin yang mewakili hak- hak masyarakat dalam pemerintah. Keputusan MK No.65/PUU-XXI/2023   sejalan dengan peran siswa SMA/MK sebagai agent of control yang bertanggung jawab mengawasi jalanya demokrasi Pancasila. Pentingnya sosialisasi dan regulasi dari pemerintah bagi sekolah-sekolah SMA/MK sebagai pelaksanaan atas putusan MK.